Чернігівський Спасо-Преображенський собор за кліровими відомостями ХІХ – початку ХХ ст. - Ванжула, О.М. (Сіверщина в історії України, 2021)
Стаття присвячена вивченню маловідомих аспектів із історії чернігівського Спасо-Преображенського собору, що базуються на
аналізі клірових відомостей ХІХ – початку ХХ ст. Клірові відомості були важливими документами церковного діловодства суворої
звітності, які надають можливість прослідкувати доволі цікаву динаміку розвитку церковної парафії Спасо-Пеображенського собору,
джерела його утримання та темпи зростання соборного капіталу,
деталізувати біографічні дані священнослужителів та з’ясувати їхній статус у загальноєпархіальній церковній ієрархії. Проаналізовано інформаційний потенціал відомостей, зміни у їхній структурі та
змісті упродовж зазначеного періоду. The article is devoted to the study of little-known aspects of the history of
the Cathedral of the Transfiguration of Our Savior in Chernihiv, based on the
analysis of the clergymen’s registers of the 19th – early 20th centuries. The clergymen’s
registers were important documents of church paperwork, which provided
an opportunity to trace the dynamic of development of the church parish,
analyze the sources of support and growth of the cathedral capital, detail the
biographical information on clergy and figure out their status in the diocesan
hierarch. They were an annual reporting documents that recorded the state of
the parish for the current year. The article analyzes the information potential
of clergymen’s registers, changes in their structure and content during the 19th
– early 20th centuries. Step-by-step they became more informative and meaningful.
Analyzing the clergymen’s registers of the Cathedral of the Transfiguration
of Our Savior in Chernihiv in certain years, we can clearly see the increase
of the information content of its historical part, track the trends of growing of
the clergy staffing establishment, the cathedral capital in securities which provides
an opportunity to buy housing for representatives of the cathedral clergy,
to build outbuildings at the expense of the cathedral in the early 20th h century.
The steady trend towards concentration among the staff of the Cathedral
of the Transfiguration of Our Savior of the best representatives of the diocesan
clergy, who took an active part in public and general diocesan life, were members
of religious and educational societies and organizations can be tracked.
There was a women’s church-parish school, a shelter for orphaned boys, which
were maintained at the expense of the cathedral, a library at the cathedral in
the early 20th h century. Thus, further study of church reporting documents is
a promising area of research on the history of a particular church.